The relationship between the attachment styles of the adults with and without depression and the parenting attitudes of their parents - Bıyık, Büşra Sümeyye; Akkaya, Cengiz (The European Research Journal, 2020)
Objectives: In this study, it is aimed to determine the relationship between attachment styles of adults with and without depression and child rearing attitudes of their parents. Methods: One hundred eighteen patients who are admitted to outpatient clinic of Department of Psychiatry of the Uludağ University School of Medicine, who are diagnosed with depression according to DSMIV-R and DSM V and put on regular medication, and 130 healthy individuals of similar demographic characteristics without any psychopathologic diagnostic, are included in this study. Within the scope of this research "Experiences in Close Relationships Inventory-II", "Child-Rearing Attitudes Scale", "Beck Depression Inventory" and Sociodemographic Information Form were used. Results: It is found that there is a significant difference between the attachment styles of the individuals with and without depression and their parents’ attitudes towards child rearing. Maternal and paternal acceptance / interest scores of the patient group were lower than those of the healthy group, and the parents’ supervision / control scores were higher. The anxiety and avoidance attachment scores of the married individuals of the patient group are higher than the scores of married individuals of the healthy group. Conclusions: High anxiety and avoidance related to attachment and controlling parental attitudes were found to be risk factors for depression.